Reaksi Pasar Modal Indonesia Terhadap Peristiwa Coronavirus Disease 2019 (Covid-19) (Event Study Pada IHSG Periode 25 Februari -6 April 2020) - VITA ARDIYANTININGSIH JARWANTO (Management and Sustainable Development Journal, 2022)
The purpose of this study is to determine the impact of the covid-19 virus outbreak on the capital market reaction that occurred on the IDX and provide information on the state of the capital market during the covid-19 virus outbreak and as a reference in making decisions for investors. This study uses secondary data obtained from the IDX publication and yahoo finance.com. The research sample used 45 stocks from nine sectors listed on the IDX, namely 1). agricultural sector, 2). mining sector, 3). basic industrial sector and chemicals, 4). various industrial sectors, 5). consumer goods industrial sector, 6). property, real estate and building construction sectors, 7). infrastructure, utilities and transportation sectors, 8). financial sector, 9). trade, service and investment sectors. The results or findings of this study indicate that 9 stock sectors were affected due to the Coronavirus Disease 2019 (Covid-19) outbreak. What is seen from the movement of stocks in the period February 25 - April 6, 2020. By using the abnormal return calculation.